Cervical aortic arch in the pediatric population: a meta-analysis of individual patient's data - Baudo, Massimo; Varrica, Alessandro; Reali, Matteo; Saracino, Antonio; Carminati, Mario; Frigiola, Alessandro; Giamberti, Alessandro; Lo Rito, Mauro (Frontiers in Cardiovascular Medicine, 2023)
Background: This is the first meta-analysis to analyze all published pediatric cases of cervical aortic arch by highlighting the clinical characteristics and treatment outcomes using the reported individual patients' data. We aimed to investigate clinical features and surgical outcomes of such a rare disease in the pediatric population. Methods: PubMed, ScienceDirect, SciELO, DOAJ and Cochrane Library databases were searched until June 2022 for case reports describing the presence of cervical aortic arch in the pediatric age. Case reports and series were included if the following criteria were met: 1) description of the cervical aortic arch; 2) patient of pediatric age; 3) English language. Exclusion criteria for analysis were all other forms of papers that did not have individual patient data. This systematic review was conducted according to the PRISMA guidelines. The primary endpoint of the analysis was early and late mortality. Results: The literature search identified 2272 potentially eligible articles, 72 of which met our inclusion criteria with 96 patients including the Author's institutional case. At a median of 365 days, the overall cohort registered 7.3% (7/96) mortality, while the only surgical one 7.3% (4/55), and mortality after surgery to treat only CAA was 2.4% (1/42). Dyspnea was identified as an independent determinant of mortality by univariable Firth bias-reduced logistic regression. Conclusion: Cervical aortic arch is a rare congenital heart disease that poses treatment challenges due to the high anatomical variability, clinical presentation, and other concomitant diseases. The surgical treatment seems safe and resolutive of the symptoms, although it needs to be tailored individually.